Correction: ESIPT-based ratiometric fluorescence probe for the intracellular imaging of peroxynitrite. Issue 25 (12th March 2019) - Wu, Luling; Wang, Yang; Weber, Maria; Liu, Liyuan; Sedgwick, Adam C.; Bull, Steven D.; Huang, Chusen; James, Tony D.
Abstract : Correction for 'ESIPT-based ratiometric fluorescence probe for the intracellular imaging of peroxynitrite' by Luling Wu et al., Chem. Commun., 2018, 54, 9953–9956.